2020
DOI: 10.1038/s41392-020-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

The Ap-2α/Elk-1 axis regulates Sirpα-dependent tumor phagocytosis by tumor-associated macrophages in colorectal cancer

Abstract: The inhibitory receptor signal regulatory protein-α (Sirpα) is a myeloid-specific immune checkpoint that engages the "don't eat me" signal CD47, which is expressed on tumor and normal tissue cells. However, the profile and regulatory mechanism of Sirpα expression in tumor-associated macrophages (TAMs) are still not clear. Here, we found that the expression of Sirpα in TAMs increased dynamically with colorectal cancer (CRC) progression. Mechanistically, CRC cell-derived lactate induced the nuclear translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
(48 reference statements)
2
23
0
Order By: Relevance
“…With our improved understanding of TAM function and mechanisms in CRC, more promising therapies based on different principles are on the way. Recent studies have shown that TAMs can express PD-1, PD-L1, and myeloid-derived specific immune checkpoint signal regulatory protein-α (SIRPα) in the TME of CRC [171]. Therefore, immunotherapy targeting TAMs may synergistically enhance the efficacy of immunotherapy with immune checkpoint inhibitors such as anti-PD-1, PD-L1, and CTLA-4 antibodies, thereby enabling more CRC patients to benefit from immunotherapy.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…With our improved understanding of TAM function and mechanisms in CRC, more promising therapies based on different principles are on the way. Recent studies have shown that TAMs can express PD-1, PD-L1, and myeloid-derived specific immune checkpoint signal regulatory protein-α (SIRPα) in the TME of CRC [171]. Therefore, immunotherapy targeting TAMs may synergistically enhance the efficacy of immunotherapy with immune checkpoint inhibitors such as anti-PD-1, PD-L1, and CTLA-4 antibodies, thereby enabling more CRC patients to benefit from immunotherapy.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…The BRAF V600E mutation in PCP may phosphorylate MAPKs to activate ELK1 and ESSRA 48,49 . Interestingly, ELK1 plays a role in the regulation of immune cells in tumor microenvironments 50,51 . Moreover, ERR1 is associated with the regulation of the balance between tumor cytolytic lymphocytes and immunosuppressive M2 macrophages in melanomas 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have demonstrated that the inhibition of the CD47-signal regulatory protein-α (Sirpα) signaling is a promising target for activating macrophage phagocytosis. Representing a “don’t eat me” signal, CD47 is overexpressed on the surface of cancer cells in many tumor types [ 54 ]. When Sirpα from macrophages binds to CD47, it controls and blocks the activation of macrophage phagocytosis [ 55 ].…”
Section: Nanoparticles For Targeting Tamsmentioning
confidence: 99%